LB-003 The Role Of Optineurin In Macrophage Cytokine Secretion And Bowel Inflammation. (9th June 2014) - Chew, TS; Sewell, GW; O'Shea, NR; Bloom, SL; Segal, AW; Smith, AM
Abstract : Abstract published in/presented at: Presented at Keystone Symposia February 2014. Introduction: Crohn's disease (CD) is a chronic inflammatory disease of the gastrointestinal tract. We previously showed that macrophages from CD patients secrete lower levels of proinflammatory cytokines due to vesicle trafficking defects, 1 which may be responsible for the deficient neutrophil recruitment in bowel 2 and decreased bacterial clearance observed in CD patients compared to healthy controls (HC). 1, 2 To investigate the low cytokine secretion, we performed transcriptomic analysis in CD and HC macrophages and identified a subgroup of CD patients with low expression of optineurin (OPTN). Methods: Optn -/- and Optn +/+ littermate mice were gavaged with Citrobacter rodentium, which induces a colitis. Bone marrow derived macrophages were stimulated with heat-killed E. coli (HkEc) then TNF and IL6 gene expression and cytokine secretion were measured. Confocal microscopy of TNF and early endosome antigen 1 (EEA1) was performed. HkEc stimulated macrophages were inhibited with lysosomal inhibitors monensin, chloroquine and NH4 Cl to investigate defective vesicle trafficking. Results: The C. rodentium colitis resulted in greater weight loss (p < 0.0001) and mortality (p = 0.007) in the Optn -/- mice. This was associated with decreased serum TNF (p = 0.03) and IL6 (p = 0.02) levels in the Optn -/- mice despite similar levels of bowel TNF and IL6 mRNA expression. Importantly this was associated with an early decreased neutrophil recruitment to the bowel on FACS in the Optn -/- mice (p = 0.02) that may account for the later greater colitis on histological colitis scores (p = 0.04). Optn -/- macrophages secrete less TNF (p = 0.006) and IL6 (p = 0.02) despite similar levels of mRNA expression. Confocal microscopy of TNF and EEA1 showed decreased colocalisation of TNF and the endosomal compartment in Optn -/- macrophages (p = 0.04) after bacterial stimulation. Lower intracellular TNF levels in Optn -/- macrophages (p = 0.03) were normalised to wildtype levels when lysosomal inhibitors were added suggesting that TNF is mistrafficked in Optn -/- macrophages to lysosomes. Conclusion: OPTN has a known role in vesicle trafficking and bacterial handling. 3, 4 The C. rodentium colitis model shows that OPTN plays a role in enteric bacteria handling, most likely via defective cytokine secretion of tissue resident macrophages. This defect is likely due to impaired trafficking of TNF from the Golgi complex to the endosomal compartment. Diminished OPTN expression in humans may increase the risk of developing CD via impaired cytokine secretion and defective bacterial clearance. Disclosure of Interest: None Declared.